MEDIA BOARD GAME UNTUK KETERAMPILAN BERBICARA BAHASA JERMAN KELAS XI SEMESTER 1 SMA YASMU MANYAR GRESIK - BADRIYAH, LAILATUL (LATERNE, 2018)
ABSTRACT Board Game Media For German Speaking Skills for 1st semester of XIth Grade Students of Yasmu Senior High School Manyar Gresik The four main components of language skills consist of listening, reading, speaking and writing. One of the most important skills is speaking ability because this skill are productive and can be used for the whole interacting processes. Based on the interviews with German teachers from Yasmu Senior High School, it can be concluded that students have difficulty to master a number of vocabulary as a material to be used for developing their speaking skills. Therefore it required an appropriate supporting media as a matter for developing German speaking skills. This reason become a fundamental basis for the development of Board Game media in order to develop German speaking skills. Through this media, it is expected in this research and development that the learning process will become more attractive and the students can easily master the vocabulary. The method used is the development of Research and Development theory (R & G) by Borg and Gall. The research stages, including: 1) potentials and problems, 2) data collection, 3) product design, 4) Design validation. The Board Game media development has been completed. The results of the analysis concluded that the development of the Board Game media was proper enough to be used. This is indicated by the validation results made by 2 experts namely 1 media expert and 1 material expert. Validation results conducted by material experts and media experts showed a value of 97.3% and 93.3% which can be generally categorized as very strong. This value qualifies the minimal category of a media which is considered as properly feasible, or categorized as a very strong criteria. Keywords: research and development, board games, speaking skills